Mobile-Augmented Reality Framework for Students Self-Centred Learning in Higher Education Institutions - A. F. Bulagang; Aslina Baharum (2018)
Objectives: To present the enhanced framework from developing a mobile-Augmented Reality (mAR) application used in the data collection at five Universities. Methods: Quantitative method was conducted with students using questionnaire that covers Effectiveness, Self-Efficacy, Motivation, Satisfaction and Features. Findings: mAR in education help increase the student performance through visualization. Application: The framework is designed to allow future and current developer to heavily focus on sections that works best with student to help and assist them in their learning session.